Cognitive and structural predictors of novel task learning, and contextual predictors of time series of daily task performance during the learning period - Smith, Evan T.; Skolasinska, Paulina; Qin, Shuo; Sun, Andrew; Fishwick, Paul; Park, Denise C.; Basak, Chandramallika (Frontiers in Aging Neuroscience, 2022)
Investigation into methods of addressing cognitive loss exhibited later in life is of paramount importance to the field of cognitive aging. The field continues to make significant strides in designing efficacious cognitive interventions to mitigate cognitive decline, and the very act of learning a demanding task has been implicated as a potential mechanism of augmenting cognition in both the field of cognitive intervention as well as in studies of cognitive reserve. The present study examines individual-level predictors of complex skill learning and day-to-day performance on a gamified working memory updating task, the BirdWatch Game, intended for use as a cognitive intervention tool in older adults. A measure of verbal episodic memory as well as the volume of a brain region involved in verbal working memory and cognitive control (the left inferior frontal gyrus) were identified as predictors of learning rates on the BirdWatch Game. These two neuro-cognitive measures were more predictive of learning when considered in conjunction than when considered separately, indicating a complimentary effect. Additionally, auto-regressive time series forecasting analyses were able to identify meaningful daily predictors (that is, mood, stress, busyness and hours of sleep) of performance-over-time on the BirdWatch Game in fifty percent of cases, with the specific pattern of contextual influences on performance being highly idiosyncratic between participants. These results highlight the specific contribution of language processing and cognitive control abilities to learning of the novel task examined in this study, as well as the variability of subject-level influences on task performance during task learning.